Early Studies in Romanesque Architecture and the Discovery of the Pilgrimage Routes to Santiago de Compostela - Henrik Karge (Ad Limina, 2025)
Since Émile Mâle’s book L’art religieux du XIIe siècle en France (1922) and Arthur Kingsley Porter’s ten-volume work Romanesque Sculpture of the Pilgrimage Roads (1923), the pilgrimage routes to Santiago de Compostela have been the subject of many studies on medieval culture. In the nineteenth century, the early days of art history as an academic discipline, the situation was quite different: the architectural heritage of the Middle Ages in France and Spain was almost exclusively studied in a national context, with the Islamic culture of Al-Andalus being the main focus in Spain. An important impetus for linking Santiago de Compostela with Saint-Sernin in Toulouse came from outside, through George Edmund Street’s Some Account of Gothic Architecture in Spain (1865). The camino de Santiago was discovered as a central theme after (1) the Archbishop of Santiago ordered the excavation of the mausoleum containing the remains of the apostle James in 1878, thereby reviving the largely dormant pilgrimage to Compostela, and (2) Fidel Fita published the first edition of the Pilgrim’s Guide of the Codex Calixtinus in 1882, with descriptions of the various pilgrimage routes. The first convincing link between the historical phenomenon of the Way of St. James and artistic connections across the Pyrenees was made by Auguste Bouillet in his essay of 1893 “Sainte-Foy de Conques, Saint-Sernin de Toulouse, Saint-Jacques de Compostelle”. Since then, art on the pilgrimage routes to Santiago has become one of the most important transnational topics in art history, although the canonization of the routes described in the Codex Calixtinus has since been shown to be problematic.